2018
DOI: 10.20998/2522-9052.2018.4.09
|View full text |Cite
|
Sign up to set email alerts
|

Method of Collaborative Filtration Based on Associative Networks of Users Similarity

Abstract: METHOD OF COLLABORATIVE FILTRATION BASED ON ASSOCIATIVE NETWORKS OF USERS SIMILARITY The subject matter of the article is the processes of generating a recommendations list for users of a website. The goal is to develop the new method of collaborative filtering based on building associative networks of users similarity to improve the quality of recommender systems. The tasks to be solved are: to develop the method of collaborative filtering based on building associative networks of user similarity, develop sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Analysis of the literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] showed that there are currently many methods and models for improving the quality of recommendation systems. One of the main ways to achieve this is to use hybrid RSs.…”
Section: Quality Characteristics Of Recommendation Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of the literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] showed that there are currently many methods and models for improving the quality of recommendation systems. One of the main ways to achieve this is to use hybrid RSs.…”
Section: Quality Characteristics Of Recommendation Systemsmentioning
confidence: 99%
“…In neighborhood-based models of recommendation systems [1][2][3][4][5], the creation of a user recommendation list can be divided into three separate processes:…”
Section: Quality Characteristics Of Recommendation Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…If for a particular user it was not possible to identify similar users, then it is not possible to form recommendations list based on collaborative filtering for him. In such cases, additional information is used, for ex-ample, contextual information, or information about social connections, or content filtering [1,4], and it was also suggested to determine a missing similarity coefficients between users through using associative networks [7].…”
Section: The Main Materialsmentioning
confidence: 99%
“…Characteristics of the network of social interactions contain balance and transitivity; force of a user's structural position; states of dyads; the influence of the network structure on model p; probability of the existence of relations between users; dependent and independent edges of the graph; evaluation of parameters of a model; logit models [23]. Scientists gradually approached determining the parameters of information security in social networks, in particular, articles [24,25] study the parameters of trust, papers [26,27] deal with joint filtering based on the construction of associative networks of users similarity. Some researchers have moved to studying the impact of specific social network parameters directly on information security parameters where it is proved that the protection system is nonlinear [28].…”
Section: Introductionmentioning
confidence: 99%